Benign schwannoma of the abdominal wall: A rare case report and a review of literature - Basu, Shouptik (Indian Journal of Case Reports, 2018)
Tumors of the peripheral nerve sheath (neurilemmomas or schwannomas) are uncommon, affecting approximately 5% of adults.The incidence of such a tumour over the abdominal wall is extremely rare. They are mostly benign and require complete surgicalexcision to prevent a sequel. Here, we report a single case of a 22-year-old male presenting with a lump over the left flank and wastreated in our teaching medical institution in Eastern India. Various imaging modalities (ultrasonography and magnetic resonanceimaging) were used to diagnose this tumor, before it was surgically excised. Histopathology confirmed the swelling to be a benignschwannoma of the abdominal wall. We have also reviewed the literature associated with this rare clinical entity. To the best of ourknowledge, only a handful of case reports on abdominal wall schwannomas have been reported so far.